Model mass spectrometric study of competitive interactions of antimicrobial bisquaternary ammonium drugs and aspirin with membrane phospholipids - Pashynska, V.A.; Kosevich, M.V.; Gomory, A.; Vekey, K. (Вiopolymers and Cell, 2013)
The aim of the study is to reveal molecular mechanisms of possible activity modulation of antimicrobial bis-quaternary ammonium compounds (BQAC) and aspirin (ASP) through noncovalent competitive complexation under their combined introduction into the model systems with membrane phospholipids. Methods. Binary and triple systems containing either decamethoxinum or ethonium, or thionium and aspirin, as well as dipalmitoyl-phosphatidylcholine (DPPC) have been investigated by electrospray ionization mass spectrometry. Results. Basing on the analysis of associates recorded in the mass spectra, the types of nonocovalent complexes formed in the systems studied were determined and the supposed role of the complexation in the BQAC and ASP activity modulation was discussed. The formation of associates of BQAC dications with ASP anion is considered as one of the possible ways of deactivation of ionic forms of the medications. The formation of stable complexes of BQAC with DPPC and ASP with DPPC in binary systems as well as the complexes distribution in triple-components systems BQAC:ASP:DPPC point to the existence of competition between drugs of these two types for the binding to DPPC. Conclusions. The results obtained point to the competitive complexation in the model molecular systems containing the BQAC, aspirin and membrane phospholipids. The observed phenomenon testifies to the possibility of modulating the activity of bisquaternary antimicrobial agents and aspirin under their combined usage, due to the competition between the drugs for binding to the target membrane phospholipid molecules and also due to the formation of stable noncovalent complexes between BQAC and ASP.